Integration of the Ntek Dulang Tradition in Thematic Learning to Foster a Sense of Togetherness in Elementary School Students - Jeni Rahma Dani; Sukron Fujianturrahman; Syafrudin Muhdar (Universitas Pendidikan Ganesha, 2026)
The decline of togetherness values among elementary school students in the era of globalization highlights the need for contextual and character-oriented learning approaches. This study aims to analyze the application of the Ntek Dulang tradition in thematic learning as a strategy to foster a sense of togetherness among elementary school students. This research employed a qualitative descriptive approach involving participants consisting of teachers, school leaders, students, and community figures selected purposively based on their relevance to the study. Data were collected through participatory observation, in-depth interviews, and documentation using observation guidelines, interview protocols, and documentation formats. Data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that the Ntek Dulang tradition possesses strong pedagogical relevance as a local wisdom-based learning medium that creates contextual, participatory, and meaningful learning experiences, contributing to the enhancement of students’ social skills and character development. Direct student involvement in cultural practices fosters cooperation, empathy, and social awareness. The study concludes that Ntek Dulang can be positioned as a transformative learning resource in strengthening character education; however, its implementation requires systematic development through structured learning models and sustainable integration into educational practices to maximize its impact.